Current Full‐Waveform Inversion of the Return Stroke Channel Based on Single‐Station Electric Field Observations. Issue 10 (23rd October 2018) - Wang, Caixia; Sun, Zhuling; Tian, Yangmeng; Liu, Mingyuan
Abstract: Because it is difficult to directly measure lightning currents, the waveform inversion of currents using easily measured electromagnetic field data is important and useful. In this paper, existing transmission models for return stroke currents are used through simulation research and comparative analyses, which results in a mixed model of transmission line model and modified‐transmission line linear model. This model is combined with mathematical expressions proposed by Heidler to represent the typical waveform of a return stroke current using an electric field calculation theory, which is generated by lightning discharge and is based on Maxwell equations; through a constraint nonlinear optimization using the Matlab software, a new method for the inversion of base current waveforms in the return stroke channel with single‐station electric field data for the return stroke is proposed. The inversion results are in good agreement with the experimental data. The inversion results show that the inversion method and the algorithm are feasible; the proposed mixed model of the transmission line and the modified‐transmission line linear may be reasonable, and the current in the channel may be divided into two parts: one part does not change with height and the other part linearly attenuates with height during the return stroke. Key Points: A mixed current transmission model for return stroke channel is proposed based on the simplest TL model and the most reasonable MTLL model A new method for inversion of base current waveform in a return stroke channel with single‐station electric field data is proposed The base current waveform of return stroke channel is retrieved; the inversion results are analyzed and summarized